Seafarer training and rural development in China: a survey report - Wu, Bin; Robinson, Bernadette; Chen, Aijuan; Li, Pinfang (National University of Singapore, East Asian Institute, 2014)
So far, most studies of the relationship between migration and development in rural China pay attention to rural-urban migration. As a consequence, less is known about international labour migration and access to it by sending communities. This phenomenon has two aspects: international chain migration via social networks, which happen mainly along coastal areas; and international contract labour migration from the poor areas of inland China. The research reported in this article examines the latter, exploring how the rural poor gain access to opportunities, what they cost and what their perceived benefits are.